PENDAMPINGAN MAHASISWA DALAM MENCIPTAKAN INOVASI USAHA WISATA KULINER BERBASIS MAKANAN TRADISIONAL DAN KEKINIAN - Sabillah, Bellona Mardhatillah; Wahyu Muh. Syata; Konstantina Ohoiwutun; Elsiana Poli (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This culinary activity as a form of community service was carried out by PGSD students at Megarezky University. The purpose of this activity is to strengthen the relationship between students from different classes and lecturers through cooking activities and art performances. The implementation of the activity consists of three stages, namely preparation, socialization, and implementation. The results of the activity showed an increase in student participation and enthusiasm, as well as the creation of a strong family atmosphere. This activity also encourages the preservation of local culinary and the development of student creativity. Thus, this culinary activity is not only an event, but also a means of education, culture, and development of students’ entrepreneurial potential. In addition, this activity opens up space for students to develop an entrepreneurial spirit, especially in the culinary field, by learning to serve food that is attractive in taste and appearance. This process is a real exercise in entrepreneurship and managing small businesses, which is very relevant in the development of a creative economy based on local culture. Thus, this culinary activity has a strategic value as a contextual learning medium that is holistic, integrative, and has a positive impact on the development of soft skills of PGSD students at Megarezky University.